Spatial modeling of the nonstationary processes of boiling liquid outflows from high pressure vessels - Bolotnova, Raisa Khakimovna; Buzina, Valeria Aleksandrovna (Computational Continuum Mechanics, 2014)
The nonstationary processes of boiling liquid outflows following high-pressure vessel depressurization are studied. The two-phase model of a boiling vapour-liquid mixture is extended to solve spatial problems in the case of axial symmetry, where single velocity, single temperature and single pressure approximations are valid, using a wide range equation of state for water and steam in analytical form (R.I. Nigmatulin, R.Kh. Bolotnova). Numerical simulation of two-phase processes is implemented on moving (Lagrangian) meshes using the shock-capturing method. The peculiarities of formation of boiling liquid jets during the explosive outflow of water from high pressure vessels are studied for different initial state parameters of saturation close to the thermodynamic critical point. The calculated spatial distributions of volume vapour concentration and pressure and velocity fields are presented. It has been found that the jet has a conical form when the initial saturation temperature of water is below 480 K. A further increase in the initial saturation temperature up to the critical point leads to twisting of the jet against the flow direction and to its “sticking” to the sidewall, so that the cone opening angle increases to 180°. The values of supersonic and subsonic regimes of outflow are determined using the Mach numbers. Qualitative agreement between calculated and experimental data (A.V. Reshetnikov, N.A. Mazheiko, etc.) is obtained.
Keywords: boiling liquid outflow; mathematical and numerical modeling; vaporization